Effect of CYP3A5*3 polymorphism on anti-inflamatory therapy in children with bronchial asthma - A. K. Zastrozhina; S. V. Zaitseva; E. A. Grishina; K. A. Ryzhykova; O. O. Panfeorova; S. Y. Kalenov; O. I. Soboleva; D. A. Sychyov; I. N. Zakharova (Медицинский совет, 2019)
Previous pharmacogenetic studies demonstrate significant genes’ polymorphisms effect on the efficacy and safety of pharmacotherapy, including in bronchial asthma (BA). According to the literature, there are data on the effect of polymorphisms CYP3A4*22 and CYP3A5*3 on the efficacy of inhaled corticosteroids in children with BA. Further research on the effect of pharmacogenetic features on the efficacy and safety of drugs is one of the way to optimize asthma therapy in children.Purpose. Identification of possible ways to optimize asthma therapy by the analysis of CYP3A5 (A6986G) gene polymorphism effect on the asthma therapy efficacy.Materials and methods. The study was conducted on the basis of three children’s polyclinics of Moscow. 100 children aged 6–17 years with an established diagnosis of BA were included. Dynamic assessment of asthma control and the amount of therapy needed was carried out. All patients underwent genotyping for the A6986G polymorphism of CYP3A5 gene by real-time PCR. Statistical data analysis was carried out using a programming language for statistical data processing R.3.4.0.Results. It was found that 8% of children with asthma were heterozygous for the A6986G polymorphism of the CYP3A5 gene, 92% of respondents were homozygous with the GG genotype. In 6 out of 8 heterozygotes, the amount of control therapy corresponded the third and fourth therapy stages according to GINA criteria. In the group of moderate and severe BA, the number of heterozygotes for the A6986G polymorphic marker of the CYP3A5 gene was statistically higher compared to the group of children with mild BA (p = 0,048).Conclusion. Thus, we identified a statistically significant difference in the occurrence of heterozygotes for the A6986G polymorphism of the CYP3A5 gene between groups of children with mild asthma and patients with moderate and severe asthma. The AG genotype and the presence of the A allele (CYP3A5 gene (A6986G)) are associated with more severe BA and the need for more anti-inflammatory therapy.